Validitas Konstruk Skala Penyesuaian Diri pada Mahasiswa - Shofia, Adinda; Nawangwulan, Meirista Dian (Universitas Pendidikan Muhammadiyah Sorong, 2021)
Self adjustment scales in college students have been generated by recent psychological research. However, the analytical method used is still using However, the analytical method still uses the classical theoretical approach which has limitations in exploring statistical findings of measurement. This study aims to find the construct validity of the self adjustment scale using Rasch analysis model. A total of 165 participants age 18-23 were randomly selected and completed the scale of self adjustment consist of 40 questions in 2019. Data were analyzed to explore the validity of the construct scale: fit data, dimensional data, rating scale analysis, and item analysis using the Rasch model via WINSTEP software version 5.1.7.0. The findings indicate that the data can be analyzed using Rasch analysis. The Person Separation Index (PSI) value is 2.97 which indicates that the scale has good reliability. Item analysis showed that the choice scale on items (1 to 5) was not normally distributed. Therefore, the choice must be less than 5 options so that participants can easily understand the item. The DIF analysis found 5 items consisting of gender let, therefore the next researcher had to revise or remove these items if necessary. Overall, most of the participants can easily understand the item and the item itself has good accuracy in measuring the adjustment attribute. Keywords: Rasch model, self adjustment, construct validity.